Correlates of Follicular Helper Bias in the CD4 T Cell Response to a Retroviral Antigen - Danelli, Luca; Donnarumma, Tiziano; Kassiotis, George (Frontiers in Immunology, 2018)
CD4+ T cell differentiation is influenced by a plethora of intrinsic and extrinsic factors, providing the immune system with the ability to tailor its response according to specific stimuli. Indeed, different classes of pathogens may induce a distinct balance of CD4+ T cell differentiation programmes. Here, we report an uncommonly strong bias towards follicular helper (Tfh) differentiation of CD4+ T cells reactive with a retroviral envelope glycoprotein model antigen, presented in its natural context during retroviral infection. Conversely, the response to the same antigen, presented in different immunisation regimens, elicited a response typically balanced between Tfh and T helper (Th) 1 cells. Comprehensive quantitation of variables known to influence Tfh differentiation revealed the closest correlation with the strength of TCR signalling, leading to PD-1 expression, but not with surface TCR downregulation, irrespective of TCR clonotypic avidity. In contrast, strong TCR signalling leading to TCR downregulation and induction of LAG3 expression in high TCR avidity clonotypes restrained CD4+ T cell commitment and further differentiation. Lastly, stunted Th1 differentiation, correlating with limited IL-2 availability in retroviral infection, provided permissive conditions for Tfh development, suggesting that Tfh differentiation is the default programme of envelope-reactive CD4+ T cells.